Top Management Team Diversity and Organizational Performance: The Mediating Effect of Strategic Change - Gachugu Ehud M.; Z.B Awino; Machuki Vincent; X.N Iraki (European Scientific Journal, ESJ, 2019)
Organization ability to anticipate and respond to the existing opportunities while observing the need for change is a vital ingredient in sustaining competitiveness and viability. The contemporary organization is faced with shifting competitive and dynamic operating environment requiring regular shifts in strategy by TMT in order to enhance performance. Despite wide interest from scholars, the association between TMT diversity and strategic change and how this influence performance is unclear. This study sought to examine the influence of TMT diversity on performance of Public Benefit Organizations (PBOs) in Kenya and the intervening effect of strategic change. The study relied on the resource based view and upper echelons theories to offer the foundations of the assessment. A cross sectional research design within a positivistic framework was adopted for the study. A sample of 138 respondents was acquired from National and International PBOs. Quantitative and qualitative data collected was analyzed using descriptive and inferential statistics. It was found that TMT Diversity statistically significantly explains 10.4% of the variability in PBO Performance. Further findings were that TMT diversity only explains 2.8% of the variability in Strategic Change (an effect confirmed to lack statistical significance); but when strategic change and TMT diversity were considered in a joint effect, the model was found to explain 11.5% of the variability in PBO Performance. However, the lack of statistical significance in the relationship between strategic change and TMT diversity disproved the mediating role of strategic change in the TMT Diversity and PBO performance relationship. The study therefore concludes that TMT diversity has an influence on PBO performance, though strategic change has no mediating effect in this relationship. The study recommends that the stakeholders in the sector should enhance TMT diversity in their organizations while carefully balancing the role of TMT in driving strategic change. Further studies targeting TMT diversity and strategic change in varying environments and contexts should be undertaken. The study contributes to the upper echelons theory in clarifying the impact of strategic change in TMT diversity and organization performance relationship. It further contributes to the advancement of PBO management policies and practices raising the need to consider instances where TMT diversity can drive or stifle strategic change efforts.